Parents' knowledge of their child with profound intellectual and multiple disabilities: An interpretative synthesis - Kruithof, Kasper; Willems, Dick; Etten‐Jamaludin, Faridi; Olsman, Erik (Journal of applied research in intellectual disabilities, 2020)
Background Parents’ knowledge of their child with profound intellectual and multiple disabilities (PIMD) is seen as crucial in the support and care for their child. The aim of this study was to explore the nature and transferability of this knowledge. Method We conducted an interpretative synthesis, searched PubMed, CINAHL, Philosopher's Index and PsycINFO and included fourteen studies. Results Parents’ knowledge was based on their long‐lasting and special bond with their child and described as an intuition, a gut feeling, a sixth sense and a sense of knowing. Parents applied their knowledge as experts in interpreting their child's intended communication, well‐being and pain, and as advocates opposing the more objectivist approach of medical professionals. Showing by example and passing on narratives were seen as important ways of transferring this knowledge. Conclusions Suggestions are made on how to apply and retain parents’ knowledge to improve care and support for people with PIMD.